Biosemiotic medicines: Symbolic formulations for placebo enhancements - Farzad Goli (Wolters Kluwer Medknow Publications, 2024)
The healing response is a complex and multiform procedure that involves many physical and symbolic interactions and synchronizations. In the clinical research model, certain factors are abstracted during which contextual elements, such as placebo responses and communicative factors, are excluded to reveal the pieces of evidence that are necessary for the mass production of clinical materials and methods. On the other side, clinical practice is a singular and chaotic communicative action in which we should include contextual and discursive factors for prompting proper biological as well as behavioral responses. Placebo responses, personal history and attitudes, and clinical relationships and communication are some of the contextual and individual factors that can be changed effectively if we can communicate with the symbolic and reflective matrices of clinical practice. In this article, the author introduces a biosemiotic formula for healing responses that include symbolic and reflective factors of healing response aligned with the related biological procedures. Not only are psychological interventions beneficial in mental health problems and symptom control but they could also be used as co-treatments to reinforce placebo responses and improve illness behavior and treatment narratives.